Kritik Abdul Karim Soroush Atas Sistem Al-Faqih: Teks Agama, Interpretasi dan Demokrasi - Setyawan, Cahya Edi (FIKRAH, 2017)
Soroush criticized the concept of "al-faqih territory" embodied in the system of religious democracy in Iran. The concept gives Mullah and Ulama a sole authority. Al-faqih territory which means the leadership of a jihad is a form of Syiah politics that takes place in the Islamic Republic of Iran. The government policy in the name of "God's Voice" to punish a State case. According to Soroush, this is a misconception because the government just prioritizes the interests of the State and denies the public inspirations. On this basis, Soroush wants to give Iranians an understanding of religion more truthfully, so that the people are aware that Religion (text / revelation) and knowledge of theology is different. Soroush attempts at giving reconsideration of the status of "religious ideology" to the public in order to be able to criticize the concept of government in Iran that is "al-faqih territory".